Genetically Modified Feed Crops and Feed Ingredients in Indonesia: Opportunities and Constraints of Development - Bambang R Prawiradiputra; Muharsini S (Indonesian Center for Animal Research and Development, 2013)
The opportunity of the presence of genetically modified organism (GMO) forage crops in Indonesia is quite large. Although until now there is no single forage crop awarded safely crop in Indonesia, but several crop byproducts have been used as feed ingredient. The controversy over the presence of GMO plant cannot be avoided. There are a part of communities who could not accept the presence of GMO crops for some reasons. On the other hand, the producers claimed the advantages of the GMO crops such as reducing pesticide application, reducing cost of weeding, more tolerant to biotic and abiotic stresses, and increasing production, farmer’s income and welfare. For the opponent, the main concerns are environmental issues and the possibility of emerging diseases in animal as well as human being. The Biosafety Comission through Biosafety Technical Team has the authority to recommend whether GMO food or feed (and plants) is safe or not safe to be consumed and grown in Indonesia after the assessment. Key words: GMO, forage crops, feed safety